Efeitos do uso da cannabis e da guerra às drogas sobre a saúde dos usuários - Holanda, Leonardo Carneiro (2022)
Plants of the Cannabis genus, popularly known as Weed, Marijuana, Ganja, among other names, have been cultivated and consumed in different forms centuries before the emergence of prohibitionist laws that characterize the current world scenario of drug policies. Cannabis cultivation is considered one of the earliest forms of agriculture in the world, following the first human efforts to domesticate plants. However, during its diffusion, it became criminalized and prohibited all over the world. Although prohibitionism has been showing its failure in recent years, even though it still prevails in some parts. Despite the negative connotation, it is recognizable that the consumption of cannabinoids can provide benefits to physical and mental health, even though there are studies that demonstrate possible risks and harms associated with its use. Faced with contradictory evidence and arguments, the main objective of this thesis was to understand the psychological impacts related to the use of Cannabis, in view of the current drug policy in Brazil. For that, three theoretical chapters were built, in which the use and production of Cannabis in history, the evolution of drug policies in Brazil and around the world, as well as the physical and psychological effects of marijuana use were discussed. In addition, an empirical study was carried out to evaluate the psychological effects related to the use of Cannabis, in terms of Anxiety and Depression, as the impacts of repression policies on these constructs in a sample of the general population of Brazil, including the comparison between users and non-users. No significant differences were found between mental health indicators between these groups, but it was observerd that users suffer more police stops and violences from the police. Results also showed preliminary evidence that the frequency of use was able to negatively predict anxiety levels, and that the dosage, on the contrary, positively predicted these symptoms. As for Depression, the tested model was not significant. Furthermore, the frequency of police stops had a negative association with mental health parameters. The results were discussed in light of recent literature. Notwithstanding the limitations of this research, the proposed objectives were met, providing relevant evidence about the implications related to the use of Cannabis and the impacts of practices resulting from the current Brazilian drug policy.